Measuring. Monitoring. Management. Control - S.S. Verkhushin; V.I. Mishchenko; I.V. Mishchenko; K.N. Isakov (Измерение, мониторинг, управление, контроль)
Background. The article analyzes the works devoted to modeling the process of functioning of the measuring channel of the measuring system of ground-based technological equipment. The substantiation is carried out that one of the promising directions of modeling the processes of functioning of measuring systems of ground-based technological equipment of test cosmodromes is the use of the theory of Markov and semi-Markov processes. Materials and methods. The well-known semi-Markov models are considered, which make it possible to justify the frequency of monitoring the technical condition of the measuring system of ground-based technological equipment. It is determined that all semi- Markov models are based on the well-known distribution law, however, at the design stage such an assumption is inappropriate. Results and conclusions. A model of the process of functioning of the measuring channel of a multichannel measuring system with limited information about its reliability is proposed.